Wind tunnel tests of wind action on a high-rise building - Bosak, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper summarizes the results of wind tunnel tests of a wind action on a high-rise building design in Warsaw. Measurements were accomplished in Wind Engineering Laboratory of Cracow University of Technology. Wind pressures on external surfaces of the building model were acquired. A study of the character of the wind action on a tower of the building was the main aim of the paper. A triangle shape with rounded corners of the cross section of the tower and a complex group of neighbor buildings support aerodynamic analysis in a wind tunnel. Wind pressure coefficients on the external building surfaces and the global horizontal wind action on the building tower on full scale were analyzed.